2022
DOI: 10.1002/adfm.202205364
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Asymmetry of Chiral Magnetic Domains Within a Magnetic Field

Abstract: Chiral magnetic domains are topological spin textures in which the Dzyaloshinskii–Moriya interaction assigns a given chirality to the domain walls. Notably, despite rapid progress in chiral magnetic research, one fundamental issue that remains unclear is how the chirality of chiral magnetic domains change as a magnetic field deforms the spin texture. Using spin‐polarized low energy electron microscopy, the evolution of Fe/Ni chiral magnetic stripe domains are investigated in single‐crystalline Fe/Ni/Cu/Co/Cu(0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 53 publications
(93 reference statements)
0
7
0
Order By: Relevance
“…However, in some papers, the asymmetrical v ( H x ) curves keeping strong asymmetry in the entire range of the IP magnetic fields were observed. Such asymmetrical v ( H x ) curves were observed in polycrystalline Pt/Co/Pt ,, and Ir/Co/Pt systems and in an epitaxial Pd/Co/Pd(111) system . In our previous paper, we showed that the asymmetric velocity curves of the same shape could not only be caused by the DMI but also the chiral damping effect should be taken into consideration.…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…However, in some papers, the asymmetrical v ( H x ) curves keeping strong asymmetry in the entire range of the IP magnetic fields were observed. Such asymmetrical v ( H x ) curves were observed in polycrystalline Pt/Co/Pt ,, and Ir/Co/Pt systems and in an epitaxial Pd/Co/Pd(111) system . In our previous paper, we showed that the asymmetric velocity curves of the same shape could not only be caused by the DMI but also the chiral damping effect should be taken into consideration.…”
Section: Resultsmentioning
confidence: 70%
“…According to the generally accepted definition of the homochiral Neél DWs, in large positive IP fields, H x ≫ |H D ± H B |, DW from the left (right) side of the circular domain with positive magnetization has left-handed ↓ → ↑ (righthanded ↑ → ↓) chirality. 46,47 The relation…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many techniques have been developed to modulate the magnetic domain patterns. For example, the chiral domains of magnetic films can be regulated by an applied magnetic field . The direction of stripe domains can be controllably changed by an applied current based on the interaction between spin waves and domain walls. , The distribution of magnetic domains can also be regulated by changing the temperature .…”
Section: Introductionmentioning
confidence: 99%